Cognitive Distortion and Unrealistic Expectation: A Clinical Study of Marital Dissolution - Hamra Zaheer; Amna Liaqat; Zeenat Islam; Bismillah Koasar; Abdul Aziz (Dialogue Social Science Review (DSSR), 2025)
The aim of the proposed study was to concentrate on establishing the relationship between cognitive distortions and having unrealistic expectations, and how it led to the dissolution of marriages. Purposive sampling of a group of (N=120) 66 women and 54 men was undertaken in the urban areas in Pakistan. The age of respondents ranged between 25 and 55 years; they had either experienced separation or divorce. The tools that were used in the data collection process were standardized such as the Interpersonal Cognitive Distortion Scale (ICDS), Marital Attitude Scale (MAS) and Marital Disillusionment Scale (MDS). This study discovered that there are significant and positive association among cognitive distortions, unrealistic expectations and marital dissolution which implies that the greater the irrational thinking and unrealistic belief also would be that closely-related to marital dissolution. The two variables were supported as having significant effects on divorce through the interrelationship between high expectations and cognitive distortions obtained through correlation analysis. Such findings bring out the psychological processes that interfere with matrimonial satisfaction and steadiness. The implications of the results are very practical implying that there is a need of a culturally modified therapeutic intervention that can target distorted cognitions and unrealistic marital expectations so as to improve quality of relationships and decrease marital distress. Key words: Cognitive Distortion, Unrealistic Expectation, Martial Dissolution, Cognitive-Behavior Therapy, Relationship Conflict